Pengaruh Electronic Word of Mouth (E-Wom) dan Kualitas Pelayanan terhadap Kepercayaan Konsumen pada Patuha Resort Bandung - Donny Purwoko; Zaharuddin Zaharuddin; Sitta Kusuma Freddy (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
The rapid growth of digital platforms has transformed consumer behavior in the tourism industry, particularly in the way trust is formed through online information and service experiences. In nature-based resorts, consumer trust is influenced not only by direct service encounters but also by perceptions generated through Electronic Word of Mouth (E-WOM). This study aims to examine the effect of Electronic Word of Mouth (E-WOM) and service quality on consumer trust at Patuha Resort Bandung, both partially and simultaneously. This research employed a quantitative approach with descriptive and associative designs. The population consisted of consumers of Patuha Resort Bandung, and a sample of 100 respondents was determined using the Slovin formula. Data were collected through structured questionnaires using a five-point Likert scale and analyzed using multiple linear regression with SPSS version 27. The results show that Electronic Word of Mouth (E-WOM) has a positive and significant effect on consumer trust. Service quality has a positive but statistically insignificant effect when tested partially. However, E-WOM and service quality simultaneously have a significant influence on consumer trust. The findings indicate that E-WOM plays a dominant role in building consumer trust, while service quality functions as a supporting factor that reinforces consumer experience and trust sustainability in tourism services.